The operational evidence base for delivering direct nutrition interventions in India: A desk review - Avula, Rasmi; Kadiyala, Suneetha; Singh, Kavita; Menon, Purnima (International Food Policy Research Institute, 2013)
The persistence of undernutrition in the face of India’s impressive economic growth is of enormous concern. Less than 55 percent of mothers and children receive any essential health and nutrition inputs that are critical for improving maternal and child nutrition. We conducted a desk review (1) to document the extent to which national and civil society/NGO programs in India reflect current technical recommendations for nutrition and (2) assess the operational evidence base for implementing essential interventions for nutrition in the Indian context.